Synthesis of fully bio-based poly (3-hydroxybutyrate)-oligo-2-ethyl oxazoline conjugates - Hazer, Baki; Altunordu Kalaycı, Özlem; Koçak, Fatma (Frontiers in Chemistry, 2024)
This work refers to the synthesis and characterization of poly (3-hydroxy butyrate)b-oligo (2-ethyl oxazoline) (oligoEtOx). Cationic ring opening polymerization of 2-ethyl oxazoline yielded in poly (2-ethyl oxazoline) (oligoEtOx) with hydroxyl end. Carboxylic acid terminated PHB was reacted with oligoEtOx via dicyclohexyl carbodiimide chemistry to obtain PHB-b-oligoEtOx conjugates. The obtained PHB-b-oligoEtOx conjugates were successfully characterized by 1 H-and 13 C NMR, FTIR, DSC, and size exclusion chromatography. PHB-b-oligoEtOx conjugates can be a promising biologic active materials..